IMPLEMENTASI PERMAINAN EDUKATIF BERBASIS LINGKUNGAN MELALUI PELATIHAN DAN PENDAMPINGAN BAGI GURU-GURU SD DI PEMULUTAN - Yuliza, Evi; Bangun, Putra Bahtera Jaya; Cahyono, Endro Setyo; Nurnawati, Elisa; Puspita, Fitri Maya; Octarina, Sisca; Indrawati, Indrawati (Universitas Mataram, 2025)
Learning activities at school carried out by elementary school students must sometimes be interspersed with educational games aimed at attracting students' interest and stimulating their brains and creativity. Educational games for elementary school children are games designed to stimulate and train students' brain development, foster imagination, develop students' creative thinking and improve memory. This service activity aims to introduce environmentally based educational games to teachers so that they are skilled at developing varied and interesting educational games. The method used in implementing this service activity is training and mentoring. This activity goes through three stages, namely delivery of material, discussion and evaluation. The results of this training and mentoring show that the average percentage of statement scores is 97.5%. This shows that environmentally based educational games provide cognitive, psychomotor and affective development for students, environmentally based educational games can create a pleasant learning atmosphere and provide stimulation for the development of children's abilities. Through this service activity, teachers can increase their knowledge of environmental-based educational games so that the learning process becomes interesting and fun.